Hidden public debt across European countries - Panyushkin, Alexei Filippovitch (2015)
The purpose of this paper is to analyze two out of three main types of Hidden Public Debt, Commercial Debt and Public Private Partnerships Financing Needs, across 11 European Countries between 2000-2012. When faced with the need to raise taxes or reduce spending, governments have for some time turned to a third option by resorting to off book loans and liabilities that do not appear in public accounts. Hidden public debts are those state commitments and liabilities that, despite a lack of specific allocation or inclusion in forecasts and liabilities, are assumed by the government. Amongst the major results, this article concludes that countries with stronger economies, more transparency of government expenditures and relatively high tax rate stayed in- or moved to the bucket of relatively low debt levels, namely with hidden debt below 1% of GDP. Also, the level of hidden debt within the PIIGS is twice if what the rest of the sample has.